Prepacked processed foods: accuracy of the labelled information - Albuquerque, T.G. (2019)
Introduction: The accuracy of nutritional labelling is important to establish health food policies. The European Commission on 25 October 2011, the Regulation (EU) No. 1169/2011 on the provision of food information, setting common definitions, principles and procedures was published. Above all, food information should not mislead consumers about the nature, characteristics, and food effects. Aim: The compliance between the declared and the determined values of prepacked processed foods, selected from the Portuguese market, considering the permitted tolerance limits for salt, fat and saturated fatty acids, was explored in this work.